2007
DOI: 10.1017/s135246580700392x
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Psychosis: A Pilot Study investigating the Effectiveness of a Self-Esteem Programme on the Self-Esteem and Positive Symptomatology of Mentally Disordered Offenders

Abstract: The importance of self-esteem in the development and maintenance of psychotic experiences has been shown in previous research. However, there has been little research into the role this plays in individuals with psychosis and forensic histories. The current study investigated the effectiveness of a standardized group programme for improving self-esteem in individuals with psychosis living in high security settings. Fifteen participants were included in the group programme and measures were taken to record chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 18 publications
(22 reference statements)
0
34
0
Order By: Relevance
“…One further paper (Lecomte et al, 1999) reported on a trial of a self esteem therapy intervention that was similar to the four reviewed above (Hall & Tarrier, 2003;Knight, Wykes, & Hayward, 2006;Laithwaite et al, 2007;Laithwaite et al, 2009). White et al (2011) reported on a randomised controlled trial of Acceptance and Commitment Therapy (ACT) for emotional dysfunction following psychosis, which was published too late to be included in the above study pool.…”
Section: Three Excluded Studies With Some Relevancementioning
confidence: 96%
See 4 more Smart Citations
“…One further paper (Lecomte et al, 1999) reported on a trial of a self esteem therapy intervention that was similar to the four reviewed above (Hall & Tarrier, 2003;Knight, Wykes, & Hayward, 2006;Laithwaite et al, 2007;Laithwaite et al, 2009). White et al (2011) reported on a randomised controlled trial of Acceptance and Commitment Therapy (ACT) for emotional dysfunction following psychosis, which was published too late to be included in the above study pool.…”
Section: Three Excluded Studies With Some Relevancementioning
confidence: 96%
“…Psychological therapy trials involved longer follow-up periods (up to two years) than pharmacological trials, and the majority found that reductions in depression achieved were paralleled with improvements in positive psychotic symptoms. Most of these had not sought to reduce depression specifically, although four did target self esteem (Hall & Tarrier, 2003;Laithwaite et al, 2009;Laithwaite et al, 2007;Knight et al, 2006 …”
Section: Psychological Therapy Trialsmentioning
confidence: 99%
See 3 more Smart Citations